Annual Avifaunal Population Dynamics in Two Wetlands of Achanakmar-Amarkantak Biosphere Reserve, Madhya Pradesh, India - Ahirvar, Bhairo Prasad; Yadav, Surendra Kumar; Chaudhry, Shivaji (Indian Forester, 2023)
Bird diversity is a good indicator of the health of the ecosystem. In the present study, 73 bird species belonging to 12 orders and 34 families with total 582 individuals were recorded using field observations from July 2018 to February 2019 (monsoon and winter). The current study was carried out to explore the avifaunal diversity around the two wetlands of Achanakmar Amarkantak Biosphere Reserve. Passeriformes are the dominant order, and Motacillidae is the dominant family from widespread taxa. The study reveals that high bird diversity (H’ = 3.65) and high evenness (J = 0.90) are recorded at Johila dam, and low evenness (J = 0.84) were recorded at the Vivekanand dam study site. High species richness (Sr =50) was recorded at Johila dam. Bird diversity and abundance vary with season and place. Both study sites are located at different altitude and have different landscapes, which may influence bird species diversity. The study sites need prominent attention for a further study concerning ecology and behavior of the avifauna.